Cape Verde: the Case for Euroization - João Loureiro (2009)
After 10 years of a fixed exchange rate against the euro and a deepening integration with the European Union (EU), the authorities of Cape Verde maintain a strong commitment to nominal stability and are now considering the official euroization of the country. Compared to the current pegging, euroization could be costly if the economic conditions of Cape Verde were to require control over the interest rates and the exchange rate. Given the strong economic and financial integration between Cape Verde and Europe, and the fact that Cape Verde records inflation rates at levels that are similar to those of the European Monetary Union (EMU), the relevant issue is whether the European Central Bank (ECB) monetary policy fits the needs of Cape Verde. In order to answer this question, we empirically assess the synchronization between the business cycle of Cape Verde and the business cycle of the EMU. For that purpose, we compute output gaps and then use conventional correlation measures as well as other indicators recently suggested in the literature. Replicating the methodology for each of the current 27 EU members, our results show that Cape Verde ranks better than several EU countries and even better than some EMU countries. We thus argue that there is a strong case for the euroization of Cape Verde. Euroization would secure the benefits already attained with the pegging to the euro and would warrant additional benefits, most likely with no relevant costs stemming from inappropriate ECB monetary policies.